Spectral Efficiency Analysis for Uplink Multi Cell Massive MIMO Cellular Communication System under Rician Fading Channels - Yibeltal, Abebaw (My University, 2023)
Massive MIMO is a technology that expands on traditional MIMO by utilizing massive number of antennas attached to a BS to serve higher number of UEs simultaneously with the same time and frequency resources. However, this technology faces several challenges such as acquiring channel state information, PC, Latency, and complexity. With the high traffic demands of cellular BS and wireless LANs, higher area throughput is required. However, the available resources such as bandwidth and cell density are reaching their limits, making the system more expensive and decreasing the signal-to-noise ratio. To address this issue, we proposed a technique to improve the spectral efficiency of multi-cell massive MIMO networks under fading channels. This technique utilizes to reduce the challenges of channel estimation while considering a ZF uplink combiner technique to mitigate inter-cell interference. The proposed model, which considers a multi-cell scenario, has been shown to improve the spectral efficiency of massive MIMO systems. By using efficient , multiple BS antennas, serving a large number of UEs per cell, and optimizing MMSE channel estimation using a ZF UL combiner, the average sum SE per cell can be increased significantly. Simulation results show that the proposed technique can significantly improve the spectral efficiency of multi-cell massive MIMO networks, especially in the presence of inter-cell interference. The simulation results demonstrates that of f 3 has a better performance than other f 1,4 with a considerable number of UEs, SNR values, code block length and BS antenna numbers with proposed ZF-MMSE
Keywords: massive MIMO, Rician fading channels, UL spectral efficiency, MMSE, EW MMSE, LS, ZF, multi cell, fading c